Réponse :
factoriser en utilisant la forme canonique
P(x) = 4 x² - 64
= 4(x² - 16)
= 4((x - 0)² - 16)
= 4(x - 0)² - 64
= 4(x - 0 + 8)(x - 0 - 8)
= 4(x + 8)(x - 8)
f(x) = x² - 3 x + 2
= x² - 3 x + 2 - 9/4 + 9/4
= x² - 3 x + 9/4 - 1/4
= (x - 3/2)² - 1/4
= (x - 3/2 + 1/2)(x - 3/2 - 1/2)
= (x - 1)(x - 2)
h(x) = 9 x² - 6 x + 1
= 9(x² - 6/9 x + 1/9)
= 9(x² - 2/3 x + 1/9)
= 9(x² - 2/3 x + 1/9 + 1/9 - 1/9)
= 9( x² - 2/3 x + 1/9
= 9(x - 1/3)²
k(x) = x² - 6 x + 9
= x² - 6 x + 9
= (x - 3)²
Explications étape par étape